Análise dos parâmetros do modelo SWMM para avaliação do escoamento em duas bacias periurbanas em Santa Maria - RS - Bastos, Gustavo Antonio Pereira (2007)
The objective of this research was to evaluate SWMM model for the urban drainage basins Alto da Colina and Sítio do Tio Pedro at Santa Maria-RS, through the variation of the parameters involved in the calibration, searching the best representation of the processes involved in the pluvial drainage pattern. For the basin Alto da Colina the simulations had been made in separate way for the agricultural and urban part of the basin. The basin Sítio do Tio Pedro was discretizada in 11 sub-basins. The basins Alto da Colina II, Alto da Colina and Sítio do Tio Pedro have areas of 1,44, 1,89 and 0,39 km² and percentages of impervious areas of 3,82, 8,69 and 13.09% respectively. The main focus of the work was on the calibration of inundation events for the respective basins and the agreement of the involved parameters in the simulations. For the basin Alto da Colina II ten events had been selected, and for the basin Sítio do Tio Pedro eight events had been selected. In the basin Alto da Colina I the simulation it was made only for four events. Techniques of geoprocessing for the survey of the physical characteristics and the land use. Also some works of field had been carried through, with the use of topography techniques with the objective to get the representative transversal sections of the stream. The results gotten in the calibration of the parameters had been satisfactory. For the discretisation adopted in the basin Alto da Colina II it was obtained a medium correlation coefficient between the values calculated and observed of 0,94 and average error in the discharge peak and drained storage of 1,16% and 4,71% respectively for the simulated events. In the applied discretisation of the basin Alto da Colina it was obtained a medium correlation coefficient of 0,99, however with average error in the discharge peak and drained storage of 0,63% and 13,44% respectively. For the basin Sítio do Tio Pedro the medium correlation coefficient was of 0,93 and average errors in the discharge peak and drained storage of 4,43% and 5,55%, respectively. The sensitivity analysis was carried through for the basins Alto da Colina II and Sítio do Tio Pedro and the parameters that showing higher sensibility in the two basins were capacity of Infiltration (I) and the Manning s roughness coefficient for the modules Runoff and Extran, respectively.